1988
DOI: 10.1172/jci113422
|View full text |Cite
|
Sign up to set email alerts
|

Decreased proliferation, interleukin 2 synthesis, and interleukin 2 receptor expression are accompanied by decreased mRNA expression in phytohemagglutinin-stimulated cells from elderly donors.

Abstract: Using cDNA probes to human interleukin 2 (IL2) and interleukin 2 receptor (IL2R), the amount of IL2 and IL2R mRNA produced by PHA stimulated peripheral blood mononuclear cells from young (< 40 yr) and old (> 60 yr) donors was quantitated. Stimulated cell cultures from each individual were also examined for proliferative ability, expression of membrane IL2R, membrane IL2R density, and for the amount of IL2R shed into the culture supernatant. Induction of IL2 and IL2R mRNAs were decreased in cells from elderly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
2

Year Published

1995
1995
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(83 citation statements)
references
References 44 publications
6
75
2
Order By: Relevance
“…Many earlier reports using different techniques to determine serum levels of cytokines indicate that the lymphocyte's response to mitogens is impaired in elderly subjects (Murasko et al, 1986;Nagel et al, 1988;Bruunsgaard et al, 2000a). In this study, we could only detect a tendency of lymphocytes from young donors to produce more IL-2.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Many earlier reports using different techniques to determine serum levels of cytokines indicate that the lymphocyte's response to mitogens is impaired in elderly subjects (Murasko et al, 1986;Nagel et al, 1988;Bruunsgaard et al, 2000a). In this study, we could only detect a tendency of lymphocytes from young donors to produce more IL-2.…”
Section: Discussioncontrasting
confidence: 52%
“…Since not only protein levels but mRNA levels of IL2 as well are de-creased in aging (Barcellini et al, 1988;Nagel et al, 1988), reduced activation of transcription factors surely is another aspect in immunosenescence.…”
Section: Discussionmentioning
confidence: 99%
“…The very large differences in apoptosis in the older mice would mandate an equally substantial change in lymphocytic population. It has been shown that non-functional T cells increase with age in both mouse and man, though the molecular and physiologic bases for this dysfunction is not yet clear (Song et al, 1993;Nagel et al, 1988). It will be interesting to determine in the future whether specific lymphocyte subsets, defined by surface markers, occupy a major portion of the aging peripheral immune system, and whether the same cells are deficient in their response to antigenic stimulation and in apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…These immune functions are altered with aging [13,19,20,28]. The role of various isoforms of PKC in cell activation and proliferation is under intense investigation [9], but there are only a limited number of reports concerning PKC isoforms expression in lymphocytes with aging [23,29] The goal of the present study was to examine PKC isozyme distribution in resting and in CD3-stimulated lymphocytes of healthy elderly and young subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Several functions of T cells that either partially depend on PKC activity or are regulated by the activation of PKC exhibit abnormalities during aging [19,20]. For instance, T cells from elderly subjects stimulated through the TcR/CD3 complex show diminished production of IL2 and a decrease in IL2 receptor expression as well as reduced activation of the AP1 and NFxB transcription factors [21,22].…”
Section: Introductionmentioning
confidence: 99%